ROUTERS EXTENSIBLES PARA INVESTIGACIÓN - Ponce Soldevilla, Max Ever (2019)
Currently the investigation in the area of routers is carried out for tools of simulation, existing a great difference among the simulation and the real world. The investigators in this area affirm that it is necessary to count on real conditions to validate the results and not only to utilize tools of simulation. The majority of the routers are teams with designs closed, inflexible and static. To add new functionalities al router requires the access to the interfaces of the software in the road of sent of packages, but these normally do not be available. Being evident the need to count with settings that permit to complete the circle among the experimentation and the real world, this paper describes the developments open software of router, that are being carried out with the purpose of building a software of router complete that be a platform of investigation and stable implementation.